Indicadores de saúde em adolescentes e espacialização de escolas estaduais da área urbana de Santa Maria, RS - Garlet, Aline de Fátima Lago (2012)
The development of deployed technologies and the advances in the computational area have allowed to establish and to study interfaces related to both the geographic space and the health area. This research is focus on studying the adolescent, considering the adolescence according to the World Health Organization WHO as that period from 10 to 19 years old and that implies physical, psychological and social transformationsseen in different ways and times. Studies on populations that approach underweight in adolescents are still pretty limited in the nutritional education area. The general aim of this work was identifying and mapping the adolescents nutritional statusesthat are registered at the public high school in Santa Maria. In a specific way, it aimed to trace the classificatory system based on the distribution of body mass index; to carry out the anthropometric measurements of triceps and subscapular; to give information about the adolescents nutritional statuses according to demographic, socioeconomic, behavioral and dietary habits, as well as to map the adolescent s nutritional statusesspatializing them into the Santa Maria s neighborhoods with the aim of subsidizing the school lunch menu. It was done through transversal exploratory studies from October to November 2010 and from March to April 2011 with 361 adolescents of both sexes registered in ten public high schools in Santa Maria, RS, and that were spreadon different neighborhoods. The information was collected through a questionnaire and by doing an anthropometric evaluation of the subjects in the research. For the analysis, the program Statistical Analysis System (SAS, Version 9,2) was used. The results were presented through tables, graphics and pictures where they were spatialized geographically from the application ARCgis (version 9,3)and concluded in the program Corel Drow 14. The results showed that the most of the adolescents, from both sexes, are within the normal range in terms of anthropometric evaluation. In terms of feeding, although having the knowledge of what is a healthy feeding, they showed theyare influenced a lot by the family, by other groups (friends/ classmates) and also by the media. Therefore, the presented results allow us to infer that this study gives subsides to implement together with schools new nutritional programs. Healthy children and adolescents represent the improvement in the life quality for this generation in general besides assuringthis quality for the adulthood for the senior periods too.